Detection of pia2 gene polymorphism in glycoprotein III in patients with :migraine - Bhaskar, Shalini; Abdullah, Jafri Malin (Detection of pia2 gene polymorphism in glycoprotein III in patients with :migraine, 2006)
Glycoprotein lila CGP lila) is a platelet membrane receptor. which when activated leads to platelet adhesion. Platelet alloantigen <P1Al is normally represented on the GPIIIa of human platelet membrane in the more common homozygous allelic state CP1A1/A1l. or the rarer polymorphic state CP1A1/A2l. The . later polymorphism P1A1/A2 polymorphic state renders the platelet hyperadhesive leading to increased incidence of coronary events and possibly migraine as well. Migraine is also a disorder wherein platelet hyperadhesion and serotonin release have been observed. Migraine is a common headache disorder exhibiting a prevalence of 9% in the Malaysian population. This study was designed to identify the prevalence of the homozygous CP1A1/A1l and the polymorphic CP1A1/A2) state in the population at Kelantan and to determine whether the polymorphic state CP1A1/A2l is more common in our migraine patients. So far no work has been published from Malaysia on this subject. A case control study was conducted between September 2004 and October 2005. eightv (80) patien(s who fulfilled the International Headache Society (IHSl criteria for migraine with or without aura. and a group of eighty healthy volunteers were recruited for the study. The P1A1/A2 genotype pattern of all these 160 individuals was analysed by polymerase chain reaction CPCRl using the Allele Specific Oligonucleotide CASO) technique and the results compared with the nigraine symptoms in the patients concerned. ·It was found that 77 (of the 80) controls and 76 (of the 80lcases with migraine possess the homozygous (P1A1/P1A1l configuration. indicating that in the population here the homozygous state is more common (i.e present in 153 out of 160 individulas studied). Secondly. the occurrence of the P1A1/A2 polymorohism in only four (of the 80) migraine cases and also three (of the 80) controls suggest that the polymorphic CP1A 1/A2) state is not more frequent in the migraine cases. Thirdly. of the four cases positive for P1A1/A2 polymorphism three had classical visual aura (75%). Earlier studies have reported that migraine with aura has an increased familial incidence when compared with migraine without aura suggesting that migraine with aura could well be related to the inheritance of this P1A1/A2 polymorphism state. Although our findings do not totally support the hypothesis that the P1A2 polymorphism represents an added inherited platet risk factor for migraine or even migraine with aura. further searches for such a factor are clearly warrwnted. because of the familial aggregation of migraine headache cases. Thus this preliminary study shows that P1A1/A2 polymorphic state on the GPIIIa platelet membrane receptor does not increase the risk of inheriting migraine. However if present it is more likely to manifest as migraine with aura in the migraineurs with this polymorphism.